Hidden charm mesons in nuclear matter and nuclei - Cobos Martinez, J. J.; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W.; Lindote, A.; Nunes, A. S.; Santos, H. (Sissa Medialab, 2021)
Recent results for the eta(c)- and J/psi-nucleus bound state energies for various nuclei are presented. The attractive potentials for the eta(c) and J/psi mesons in the nuclear medium originate, respectively, from the in-medium enhanced DD* and D (D) over bar loops in the eta(c) and J/psi self energies. Our results suggest that the eta(c) and J/psi mesons should form bound states with all the nuclei considered